Global and Regional Burden of Seborrheic Dermatitis: Trends in Incidence and DALYs, 1990–2021 - Hao Z; Zhao X; Chen J; Li B; Xu W; Zhang L (Clinical, Cosmetic and Investigational Dermatology)
Zixiao Hao,1,2 Xinyu Zhao,3 Jiaxing Chen,3 Bingrun Li,3 Wenjing Xu,3 Litao Zhang2 1Graduate School, Tianjin Medical University, Tianjin, People’s Republic of China; 2Department of Dermatology, Tianjin Institute of Integrative Dermatology, Tianjin Academy of Traditional Chinese Medicine Affiliated Hospital, Tianjin, People’s Republic of China; 3Graduate School, Tianjin University of Traditional Chinese Medicine, Tianjin, People’s Republic of ChinaCorrespondence: Litao Zhang, Department of Dermatology, Tianjin Institute of Integrative Dermatology, Tianjin Academy of Traditional Chinese Medicine Affiliated Hospital, Tianjin, People’s Republic of China, Email zhanglitao@zohomail.cnBackground: Seborrheic dermatitis (SD) is a prevalent chronic skin condition affecting areas rich in sebaceous glands, causing significant discomfort and psychological burden. Despite its impact, detailed global burden trends remain underexplored.Methods: Data from the Global Burden of Disease (GBD) study for SD from 1990 to 2021 were analyzed, examining incidence and Disability-Adjusted Life Years (DALYs). Trends were assessed using the estimated annual percentage change (EAPC), and correlations between disease burden and socio-economic development indices (SDI) were evaluated.Results: In 2021, SD affected 135,710,441 individuals globally—an increase of 53% since 1990. Despite this growth, the global age-standardized incidence rate (ASIR) remained relatively stable at 1,704.04 per 100,000 (EAPC: 0.11183). Females showed a higher ASIR than males, while males had slightly higher age-standardized DALYs rates. The 75+ age group experienced the highest DALYs burden despite the lowest ASIR, highlighting a disproportionate impact on the elderly. Regions with higher SDI levels generally had lower incidence and DALYs rates, whereas Western Sub-Saharan Africa bore the highest burden. Nationally, Nigeria, Ghana, and Cameroon had the highest ASIRs. These findings underscore significant regional and national disparities in SD burden, even amid overall rate stability.Conclusion: Despite stable age-standardized rates, the increasing absolute burden of seborrheic dermatitis and pronounced regional disparities underscore the need for targeted public health interventions, particularly in resource-limited settings. Strengthening disease management strategies and expanding research efforts in these areas will be crucial to reducing the global impact of SD.Keywords: global burden of disease, seborrheic dermatitis, incidence, DALYs